Interactive Digital Teaching Module Based on Differentiated Instruction and Its Impact on Students' Problem-Solving Skills - Ayu Rahayu; Rosti Rosti (Postgraduate, University of Mataram, 2023)
Differentiated Instruction (DI) is a solution offered in the Merdeka Belajar curriculum, where students study chemistry material according to their abilities, what they like, and their individual needs so that they are not frustrated and feel like they have failed in their learning experience. This study aims to develop interactive digital teaching modules based on Differentiated Instruction (DI) that meet valid, practical, and effective criteria for problem-solving abilities. This research is development research based on the ADDIE model with stages: analysis, design, development, implementation, and evaluation. The trial sample was class X students of SMAN 1 Latambaga. The results showed validity with a value of 2.59, Practical with a value of 3.31 on teacher activity and a weight of 3.41 on student activity. Effective with good student response 74%. Problem-solving ability increases with a test score gain of 0.32 in the medium category. It is concluded that the interactive digital teaching module based on Differentiated Instruction (DI) can be used in the learning process because it begins with a diagnostic assessment so that learning is by students' abilities and learning styles